Manajemen Sanggar Tuah Sepakat di Lubuk Alung Padang Pariaman - Suci Surya Nila Putri; Mia Fahmiati (Lembaga Yasin AlSys, 2026)
Studies on art studio management have been widely conducted; however, discussions that specifically examine the integration of organizational governance and social media-based marketing strategies in local traditional art studios remain limited. This study aims to describe and analyze the management practices of Sanggar Tuah Sepakat in Lubuk Alung Subdistrict, Padang Pariaman Regency, particularly in terms of organizational governance and the marketing of performing arts through social media. The research employed a qualitative approach with a case study design, involving three informants selected through purposive sampling, consisting of the studio leader, music coordinator, and costume coordinator. Data were collected through direct observation, in-depth interviews, and documentation, and were analyzed using descriptive qualitative analysis through the stages of data reduction, data display, and conclusion drawing. The findings show that Sanggar Tuah Sepakat has implemented management functions—planning, organizing, actuating, and controlling—in a structured manner, thereby supporting the smooth execution of performance production, member development, and organizational sustainability. In addition, the use of social media, particularly Instagram, plays an important role in strengthening the studio’s visibility, expanding the reach of its promotional activities, and facilitating collaboration with various event partners. This study contributes to the literature on performing arts management and affirms that sound organizational governance and effective digital marketing strategies are critical prerequisites for sustaining traditional art studios amid the dynamics of the creative industries.